Indigenous Health Workforce Development: challenges and successes of the Vision 20:20 programme. (17th December 2012) - Curtis, Elana; Reid, Papaarangi
Abstract: Background: There are significant health workforce inequities that exist internationally. The shortage of indigenous health professionals within Australia and New Zealand requires action across multiple sectors, including health and education. This article outlines the successes and challenges of the University of Auckland's Vision 20:20 programme, which aims to improve indigenous Māori and Pacific health workforce development via recruitment, bridging/foundation and tertiary retention support interventions within the Faculty of Medical and Health Sciences (FMHS). Methods: Seven years of student data (2005–2011) are presented for undergraduate Student Pass Rate (SPR) by ethnicity and Certificate in Health Sciences (CertHSc) SPR, enrolments and completions by ethnicity. Four key areas of development are described: (i) student selection and pathway planning; (ii) foundation programme refinement; (iii) academic/pastoral support; and (iv) re‐development of the indigenous recruitment model. Results: Key programme developments have had a positive impact on basic student data outcomes. The FMHS undergraduate SPR increased from 89% in 2005 to 94% in 2011 for Māori and from 81% in 2005 to 87% in 2011 for Pacific. The CertHSc SPR increased from 52% in 2005 to 92% in 2011 with a greater proportion of Māori and Pacific enrolments achieving completion over time (18–76% for Māori and 29–74% for Pacific). Conclusion: Tertiary institutions have the potential to make an important contribution to indigenous health workforce development. Key challenges remain including secondary school feeder issues, equity funding, programme evaluation, post‐tertiary specialist workforce development and retention in Aotearoa, New Zealand.